POTENTIAL OF IMPLEMENTING ARTIFICIAL INTELLIGENCE AND MACHINE LEARNING IN ENHANCING HEALTHCARE OPERATIONS AND ADMINISTRATIVE PROCESSES - Nawaf Ghassab Al Harthi, Nawaf Joudallah Almutairi, Abdulamlik Salem Alsuwailim, Mohammad Ali Alharbi, Abdullah Mishal Alotibi, Nawaf Abdulaziz Aljeraisy, Turki Ahmed Ibrahim Alanezi, Samia Mohammed Alsomali, Fahad Rakan Alatawi,; Ahmed Safaq Alshammari, Ahmed Qasem Alruwaili, Mousa Ateeq Alshammari, Sami Abdulrahman Alolaiwah, Naseer Abdullah Altamimi, Sarah Atiah Mayudh Alharthi (Chelonian Research Foundation, 2022)
Professionals in the field of life sciences who specialize in Artificial Intelligence (AI) and Machine Learning (ML) are facing growing demands to expedite the development of algorithms. The potential to uncover novel insights and accelerate advancements resides in the use of extensive datasets that are integrated across several levels. Despite the abundance of available data, only a small fraction is being processed, interpreted, combined, and evaluated. This technology focuses on the examination of how computers may acquire knowledge from data and replicate human cognitive processes. AI and ML provide both an augmentation of learning capacity and the implementation of a decision support system that is reshaping the future of healthcare. This article provides an overview of the applications of artificial intelligence (AI) and machine learning (ML) in the healthcare sector. It focuses on how these technologies are used in clinical, developmental, administrative, and global health settings to enhance the overall healthcare system. The article also discusses the effects and anticipated outcomes of each aspect of healthcare. In addition, the potential future trends and applications of this technology in medical infrastructure have been addressed. Keywords: medical infrastructure, healthcare records, artificial intelligence, AI in healthcare, deep learning, machine learning, healthcare and AI